Analisis Etika Bisnis dalam Aktivitas Influencer Marketing di Era Digital Terhadap Kepercayaan Konsumen - Zulfah Nur Fauziah; Maelul Diniati; Galuh Bintang Ayuni; Sefti Vitta Sukmaning Tias; Catur Wahyudi (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
The rapid development of digital technology has encouraged the rise of influencer marketing as an effective marketing strategy for reaching consumers. However, despite its effectiveness, this practice also raises business ethics concerns, particularly related to transparency, honesty, and credibility in promotional communication. This study aims to analyze the influence of business ethics in influencer marketing activities in the digital era on consumer trust. This research uses a quantitative approach with an associative method. Data were collected through questionnaires distributed to respondents who had seen or followed influencer marketing activities on social media. The results show that business ethics has a positive and significant effect on consumer trust. In addition, influencer marketing also has a positive and significant effect on consumer trust. These findings confirm that the application of business ethics principles such as honesty, transparency, and responsibility is essential in building consumer trust in the digital era.